(untitled) (Educational Knowledge, 2014)
The work of teachers is a crucial element in the student learning process, as it largely determines whether students remain motivated throughout their time at school. This implies that teachers seek out methodological strategies, didactic resources, and incorporate technology to enhance their teaching. The research results reflect the reality within the city of Santa Ana, specifically at the basic education level, and how teachers carry out their work in the classroom. Data was also obtained on different methodologies: from the traditional approach, where the teacher delivers the lesson expositoryly, to group and individual work, and even the execution of simple experiments. All of these are incorporated into lesson planning, serving as a support tool for teachers, along with the teaching materials.